The Correlation of Exposure of Cigarette Smoke to Pregnant Women G1 with the Event of Early Rubber of Money at Harapan Insan Sendawar Hospital, Kutai Barat Regency - Lusiana; Nilam Noorma; Cristinawati Br Haloho (Formosa Journal of Sustainable Research, 2023)
Premature rupture of membranes is one of the contributors to MMR in Indonesia. Based on Riskesdas data in 2018, the prevalence of premature rupture of membranes in Indonesia is 5.6%. The purpose of this study was to determine the relationship between exposure to cigarette smoke in G1 pregnant women and the incidence of premature rupture of membranes at Harapan Insan Hospital, Sendawar, West Kutai Regency. This study used a cross-sectional study design. The population in this study were all G1 pregnant women who gave birth at Harapan Insan Sendawar Hospital, West Kutai Regency from August to December 2021, totaling 51 respondents with G1. The sample size is 51 people. The sample was selected by the total sampling method. In the intervention group, the p-value was 0.000 <0.05. Meanwhile, in the control group, the p-value was 0.771 and 0.082 > 0.05. The significance value of the posttest in the intervention group and the control group was p-value 0.000<0.05. The results of statistical tests with the Chi-Square test obtained p- value 0.010 <0.05, then H1 is accepted and H0 is rejected, and Pearson's test analysis shows that the level of strength of the relationship is 0.363. Mother's supervision and awareness is needed in avoiding cigarette smoke from before pregnancy until pregnancy and childbirth